Aerodynamic components of aircraft at high speeds - Donovan, A. F. (Allen F.); Lawrence, H. R. (Herbert R.) (High speed aerodynamics and jet propulsion, 1957)
Volume VII of the High Speed Aerodynamics and Jet Propulsion series. It deals with applications to specific components of the complete aircraft. Sections of the volume include: aerodynamics of wings at high speed, aerodynamics of bodies at high speed, interaction problems, propellers at high speed, diffusers and nozzles, and nonsteady wing characteristics. Originally published in 1957. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.